Screening of muskmelon (Cucumis melo L.) germplasm against salinity (Bangladesh Journal of Agricultural Research, 2012)
Out of 78 germplasm of muskmelon (Cucumis melo L.), 67 germplasm (86%) survived against high salinity (13.82 ds/m) when screened at Benarpota, Satkhira, Khulna. These germplasm showed morphological variations in growth habit, leaf lobes, leaf pubescence, fruit shape, fruit ribs, fruit skin texture, flesh colour, flesh flavor, flesh texture, fruit splitting, fruit aroma, fruit size, seed coat colour, fruit skin colour at fully formed fruit and fruit skin colour at seed harvest maturity. The other qualitative characters, such as tendrils and flowering habit did not show morphological variations. Quantitative variations were observed in leaf length, leaf width, days to staminate flowering, days to pistillate flowering, fruit length, fruit width, fruit weight, number of fruits per plant, flesh thickness, number of seeds per fruit, days to fruit harvest and 1000-seed weight. Among the germplasm, BD-2255 and BD-9159 had no splitting of fruits. Therefore, these two germplasm can be selected for this trait. The characters, such as number fruits per plant and fruit weight exhibited highest number of fruits per plant (21) and maximum fruit weight (6.25 kg). These two characters should also be considered for improvement of muskmelon. Highest CV (%) was found in number of fruits per plants (36.35) followed by fruit weight (33.86). Bangladesh J. Agril. Res. 37(3): 465-472, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12124